Noteworthy habitat and phylogeny updates for eastern US Ulota (Orthotrichaceae, Bryophyta). (3rd September 2017) - Tessler, Michael; Cunningham, Seth W; Clark, Theresa A
Abstract: The moss Ulota crispa is ubiquitous as an obligate epiphyte in eastern North America. Yet several specimens preliminarily identified as U. crispa were collected from the upper portions of boulders in the Shawangunks, NY. Mitochondrial ( nad5 ) and chloroplast ( rps4 and trnL-trnF ) sequence data were produced for these specimens, confirming their status as the first record of rock-dwelling U. crispa in North America. The reviewed loci were then used to assess phylogenetic relationships of Northeastern US Ulota species, incorporating a species not yet reviewed, U. coarctata . Conforming to peristome morphology, Ulota hutchinsiae appears to be more closely related to U. crispa than to U. coarctata . Monophyly was recovered for U. crispa and U. coarctata . Although monophyly was not found for U. hutchinsiae, it is diagnosably distinct based on the reviewed loci. While almost identical in number of nucleotides sequenced, mitochondrial DNA held substantially less phylogenetically informative nucleotides than the chloroplast loci, but did have important indel information segregating U. coarctata from other species reviewed.